Pengaruh Karakteristik Individu dan Iklim Organisasi Terhadap Kinerja Dosen Universitas Hang Tuah Surabaya - Yanti, Dyah Agustin Widhi (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2018)
This study aims to prove and analyze the influence of individual characteristics and organizational climate on the performance of lecturer of Hang Tuah University Surabaya. Individual characteristics: are traits - traits that distinguish one individual with another individual that is inherent to the individual and affect the work of individuals and organizations (Gibson, et al., 1990; Suprihanto, 2003; Winardi, 2004; Robbins, 2006). Individual characteristics are operationally measured using the following four dimensions: Ability, Skills, Age, Working Period Organizational climate is the atmosphere that is in the internal environment of perceived individual organizations in the work (Schneider and Hall, 1972; Campbe, et al, 1970; Litwin and Stringger, 1986; Hinggins, 1982, Limster, 1985). Organizational climate is operationally measured by the following five dimensions; Individual Autonomy, Support, Orientation on Awards, Warmth, Trust, Lecture performance. Performance is the result of individual work in the form of quantity and quality during a certain work time (Gomes, 1995; Judge 1996; Mathis and Jackson, 2002; Gibson et al, 2006; Sudiro, A., 2008; Republic of Indonesia Law No. 13 of 2005 about teachers and lecturers) Lecturer performance is measured through the following three dimensions: Education and Teaching, Research, Community Service. The population in this study were all permanent lecturers of Hang Tuah University who were permanent lecturers of foundations and permanent lecturers of the state who were assisted in PTS (lecturers of DPK) totaling 257 people. This study uses a research sample of 200 permanent foundation lecturers and permanent lecturers with the status of Civil Servants assigned to Hang Tuah University.  The results of regression equation research: Y = -11.135+ 0.493X1 + 0.165X2. Hypothesis testing: Effect of Individual Characteristics on the performance of Hang Tuah University Surabaya lecturers. The Individual Characteristics variable (X1) based on the calculation is obtained by value t count amounted to 13.010 > t table at 1.9720 with a significance level of 0000 < alpha 5% then H0 rejected and H1 accepted at a significance level of 5% so characteristic individu significant effect on the performance of a lecturer at the University of Hang Tuah. The influence of organizational climate on the performance of Hang Tuah University Surabaya lecturers. Organizational Climate Variable (X2) based on calculations obtained t count value of 5.906 > t table of 1.9720 with a significance level of 0.000 < alpha 5% then H0 was rejected and H1 was accepted at a significance level of 5% so that the Organization's Climate had a significant effect on the performance of lecturers in Hang Tuah University.